Pasteurella multocida Toxin Triggers RANKL-Independent Osteoclastogenesis - Chakraborty, Sushmita; Kloos, Bianca; Harre, Ulrike; Schett, Georg; Kubatzky, Katharina F. (Frontiers in Immunology, 2017)
Bone remodeling is a continuous process to retain the structural integrity and function of the skeleton. A tight coupling is maintained between osteoclast mediated resorption of old or damaged bones and osteoblasts mediated formation of new bones for bone homeostasis. While osteoblasts differentiate from mesenchymal stem cells, osteoclasts are hematopoietic in origin and derived from myeloid precursor cells. Osteoclast differentiation is driven by two cytokines, cytokine receptor activator of NF-κB Ligand (RANKL) and macrophage colony stimulating factor (M-CSF). Imbalances in the activity of osteoblasts and osteoclasts result in the development of bone disorders. Bacterially caused porcine atrophic rhinitis is characterized by a loss of nasal ventral conchae bones and a distortion of the snout. While Bordetella bronchiseptica strains cause mild and reversible symptoms, infection of pigs with toxigenic Pasteurella multocida strains cause a severe and irreversible decay. The responsible virulence factor Pasteurella multocida Toxin (PMT) contains a deamidase activity in its catalytical domain that constitutively activates specific heterotrimeric G proteins to induce downstream signaling cascades. While osteoblasts are inhibited by the toxin, osteoclasts are activated, thus skewing bone remodeling towards excessive bone degradation. Still, the mechanism by which PMT interferes with bone homeostasis and the reason for this unusual target tissue are not yet well understood. Here, we show that PMT has the potential to differentiate bone marrow-derived macrophages into functional osteoclasts. This toxin-mediated differentiation process is independent of RANKL, a cytokine believed to be indispensable for triggering osteoclastogenesis, as addition of osteoprotegerin (OPG) to PMT-treated macrophages does not show any effect on PMT-induced osteoclast formation. Although RANKL is not a prerequisite, toxin-primed macrophages show enhanced responsiveness to low concentrations of RANKL, suggesting that the PMT-generated microenvironment offers conditions where low concentrations of RANKL lead to an increase in the number of osteoclasts resulting in increased resorption. PMT-mediated release of the osteoclastogenic cytokines such as IL-6 and TNF-, but not IL-1, supports the differentiation process. Although the production of cytokines and the subsequent activation of signaling cascades are necessary for PMT-mediated differentiation into osteoclasts, they are not sufficient and PMT-induced activation of G protein signaling is essential for efficient osteoclastogenesis.